IT manager's handbook : getting your new job done - Holtsnider, Bill, 1956-; Jaffe, Brian D. (Boston : Elsevier/Morgan Kaufmann Publishers, 2007)
Many technical professionals are tossed into their new position of managing an IT department without enough training or experience let alone a clear idea of what is expected of them. Other technicians are trying to decide if they should join the ranks of management, and want the real facts about managing and managing other technical pros before they decide. To compound the issue, most companies have become highly dependent on their IT departments for their day-to-day business operations often including revenue generation so the tasks are critical and the learning curve is steep. The IT Managers Handbook, 2nd edition provides essential information needed to manage the new responsibilities thrust on you (or the ones you would like to have): vital tasks such as creating budgets, evaluating technologies, administering compliance, and managing staff. A completely updated and expanded second edition that provides practical, easily accessible management advice written specifically for new IT managers: Brings you up to speed on those business practices most critical to effective IT operations: recruiting, budgeting, resource planning, managing personnel, and working with vendors. Includes expanded coverage on such critical IT management topics as security, disaster recovery, storage, government/regulatory compliance, and project management. Organizes information modularly so you can delve directly into only the topics that you need. Provides a unique management perspective on those specific technical issues with the most significant business ramifications. Includes new material on key technology topics such as open source, wireless, handhelds, outsourcing, offshoring, and operations, as well as updated coverage of e-commerce, remote access, intranets, and LAN/WAN management.